2012
DOI: 10.1007/s10802-012-9654-3
|View full text |Cite
|
Sign up to set email alerts
|

Family Influences on the Long Term Post-Disaster Recovery of Puerto Rican Youth

Abstract: This study focused on characteristics of the family environment that may mediate the relationship between disaster exposure and the presence of symptoms that met DSM-IV diagnostic criteria for symptom count and duration for an internalizing disorder in children and youth. We also explored how parental history of mental health problems may moderate this meditational model. Approximately 18 months after Hurricane Georges hit Puerto Rico in 1998, participants were randomly selected based on a probability househol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
36
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 55 publications
8
36
0
1
Order By: Relevance
“…These findings are consistent with previous research showing heightened negative responses to disaster-related stimuli among older youth relative to younger children (Comer et al, 2008; Green et al, 1991), as well as work showing that adolescent symptoms, relative to the symptoms of younger children, are more likely to be influenced by family variables following a disaster (Felix, You, Vernberg, & Canino, 2013). Younger children show less sophisticated cognitive reasoning and meta-cognitive skills than older children and adolescents, and as such caregivers and professional guidelines may perceive them as needing more help comprehending and making sense of difficult events.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings are consistent with previous research showing heightened negative responses to disaster-related stimuli among older youth relative to younger children (Comer et al, 2008; Green et al, 1991), as well as work showing that adolescent symptoms, relative to the symptoms of younger children, are more likely to be influenced by family variables following a disaster (Felix, You, Vernberg, & Canino, 2013). Younger children show less sophisticated cognitive reasoning and meta-cognitive skills than older children and adolescents, and as such caregivers and professional guidelines may perceive them as needing more help comprehending and making sense of difficult events.…”
Section: Discussionsupporting
confidence: 91%
“…Prior work has shown heightened negative responses to disaster-related stimuli among older children compared to younger children (Comer et al, 2008; Green et al, 1991). Other work has shown that adolescent symptoms, relative to the symptoms of younger children, are more likely to be influenced by family variables (e.g., discipline, parent-child relationship quality, parents’ marital quality) following a disaster (Felix, You, Vernberg, & Canino, 2013). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the recovery phase, the U.S. government is required to provide housing and medical and dental care to the victims of disasters, cover funeral expenses (67, 68), and offer financial support and food coupons to unemployed and low-income people (16). In addition, psychotherapy and family therapy interventions usually are needed to protect children and adolescents during the recovery phase (69). …”
Section: Discussionmentioning
confidence: 99%
“…The decision to include a parental component was driven by literature supporting the importance of parental monitoring and parent-child communication, as well as the impact of parents’ own mental health functioning, in mitigating risk for adolescent mental health and substance use problems (Felix, You, Vernberg, & Canino, 2013; Ryan, Jorm, & Lubman, 2010; Yap, Pilkington, Ryan, & Jorm, 2014). To the authors’ knowledge, this is the first internet accessible intervention to target the family in the post-disaster context.…”
Section: Discussionmentioning
confidence: 99%